KESIAPSIAGAAN INDIVIDU TERHADAP BENCANA GEMPA BUMI DI LINGKUNGAN PUSAT PENDIDIKAN DAN PELATIHAN BADAN METEOROLOGI KLIMATOLOGI DAN GEOFISIKA - Madona, Madona (Pusdiklat BMKG, 2021)
Employees of the Center for Education and Training of Agency for Meteorology Climatology and Geophysics have two roles: one of Agency for Meteorology Climatology and Geophysics and the community in general who are expected to have adequate knowledge and skill to anticipate an earthquake. But, whether their knowledge and skill possessed are sufficient or not in dealing with the earthquake disaster. This research aims to identify an individual preparedness level for earthquake disasters in the Center for Education and Training of the Agency for Meteorology Climatology and Geophysics. The research was based on four parameters, namely 1) knowledge and attitude; 2) emergency planning; 3) warning system; and 4) resource mobilization capacity. The research which was started from February until April 2021 used the descriptive research method with the quantitative approach. The questionnaire used was the standardized questionnaire which had been developed dealing with the disaster preparedness concept by the Indonesian Institute of Sciences was collaborated with United Nations Educational and Scientific Cooperation and International Strategy for Disaster Reduction. Collecting data was conducted by distributing the questionnaire to 18 employees of the Center for Education and Training who as respondents in this research. Afterward, data which had collected was analyzed by using the tabulation frequency and cross-tabulation, diagram, as well as indexes. The results of this research were the majority of the individual preparedness level in “Sangat Siap” category (44.40 percent), whereas the majority of the preparedness level was based on four parameters had similar levels were in “Sangat Siap” category.